Penerapan Pembelajaran dalam Jaringan (Daring) di Masa Pandemi Covid-19 pada PAUD - Mutmainnah Mutmainnah; Rahmatun Nessa (Departement of Mathematics Education, 2023)
The purpose of this study was to describe the application of online learning in Al-Azhar Islamic Kindergarten, Cairo, Banda Aceh and TKIP FKIP, Syiah Kuala University. This research is a qualitative descriptive study with the research subject being the principal and 2 teachers of the Al-Azhar Islamic Kindergarten Cairo Banda Aceh and the principal and 2 teachers of Kindergarten FKIP at Syiah Kuala University. Data collection techniques using interview techniques, observation and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that the learning carried out at Al-Azhar Islamic Kindergarten Cairo Banda Aceh is online learning using mobile phones through the WhatsApp application, using worksheets and to support teacher learning using the Zoom application. Whereas the TKIP FKIP of Syiah Kuala University, the learning that is carried out is online learning using mobile phones via the WhatsApp application.